Adoption of Worldcoin digital wallet in Thailand - Tanpat Kraiwanit; Pongsakorn Limna; Peerapat Wattanasin; Saranchana Asanprakit; Ruangchan Thetlek (Research in Globalization, 2023)
In the dynamic and ever-evolving digital landscape, the emergence of digital wallets, exemplified by the likes of Worldcoin, represents a significant and transformative trend. This study employed a quantitative research approach to investigate the potential determinants of Worldcoin wallet adoption in Thailand. Data from 1,430 participants were collected through structured questionnaires, and binary regression analysis was used to examine the relationship between key independent variables, including gender, age, education, occupation, income, savings, digital wallet possession, usage frequency, and social media engagement, and the adoption of the Worldcoin wallet. The study found that all these factors significantly influenced individuals' inclination to adopt the Worldcoin wallet in Thailand. These findings carry substantial implications for promoting digital wallet adoption in Thailand. Tailoring marketing strategies to demographic groups based on variables such as gender, age, education, occupation, income, savings, digital wallet ownership, usage frequency, and social media engagement can enhance adoption rates and better meet user preferences.
Keywords: 330; Adoption; Determinants; Digital wallets; Worldcoin